2021
DOI: 10.1101/2021.01.25.21250233
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Contamination of air and surfaces in workplaces with SARS-CoV-2 virus: a systematic review

Abstract: ObjectivesThis systematic review aimed to evaluate the evidence for air and surface contamination of workplace environments with SARS-CoV-2 RNA and the quality of the methods used to identify actions necessary to improve the quality of the data.MethodsWe searched Web of Science and Google Scholar until 24th December 2020 for relevant articles and extracted data on methodology and results.ResultsThe vast majority of data come from healthcare settings, with typically around 6 % of samples having detectable conce… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 47 publications
1
12
0
Order By: Relevance
“…1,[5][6][7][10][11][12] A limited number of studies to date have recovered viable SARS-CoV-2 virus from environmental samples. 14 We attempted to recover SARS-CoV-2 virus from 42 environmental surface samples, six (14%) of which from three (4%) patients yielded viable virus; positive cultures were confirmed with SARS-CoV-2 RT-PCR. Notably, all surface samples that yielded viable virus were collected from patients within 5 days of illness onset.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,[5][6][7][10][11][12] A limited number of studies to date have recovered viable SARS-CoV-2 virus from environmental samples. 14 We attempted to recover SARS-CoV-2 virus from 42 environmental surface samples, six (14%) of which from three (4%) patients yielded viable virus; positive cultures were confirmed with SARS-CoV-2 RT-PCR. Notably, all surface samples that yielded viable virus were collected from patients within 5 days of illness onset.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6][7][8][9][10][11][12] However, a minority of studies have attempted to culture virus. 13,14 This limits our understanding of exposure and transmission risk.…”
Section: Introductionmentioning
confidence: 99%
“…We identified one non-peer-reviewed (pre-print) systematic review that assessed SARS-CoV-2 contamination in fomites 18 . The authors concluded that the quality of measurements was poor, and the reliability of the data is uncertain.…”
Section: Discussionmentioning
confidence: 99%
“…There are limited data about the exposure of workers to the SARS-CoV-2 virus. Most research concerns virus in healthcare settings, where air concentrations and surface contamination were generally low ( Cherrie et al , 2021 ). It is unclear why this is the case, but it may reflect good general ventilation and regular cleaning regimes in these workplaces.…”
Section: Methodsmentioning
confidence: 99%
“…It is unclear why this is the case, but it may reflect good general ventilation and regular cleaning regimes in these workplaces. Very limited data are available for public transportation, which also show low levels of air and surface contamination ( Cherrie et al , 2021 ). There are no data on environmental contamination for other workplace environments.…”
Section: Methodsmentioning
confidence: 99%